PELATIHAN PEMBUATAN LUBANG SERAPAN BIOPORI UNTUK PENANGGULANGAN BANJIR PADA SAAT MUSIM HUJAN DI SEKOLAH DASAR RK SANTO DANIEL DESA BATU MBELIN - Darlina Tanjung; Ahmad Bima Nusa; Kartika Sari; Yusnidah Yusnidah (Universitas Islam Sumatear Utara, 2022)
Daniel Batu Mbelin is a problem of shortage in drainage of sewerage. In the rainy season, inundation often occurs in the school environment because water is not absorbed into the soil. The purpose of this activity is: to provide insight and guidance to the community, especially the school environment to raise awareness or provide input on the problem of puddles that often occur during the rainy season, which can adversely affect the school environment as well as the health of children and the community around the school. The method of implementing this activity is to conduct counseling and training in making infiltration holes or biopore channels. The result of this activity is that the community of SD RK ST Daniel Batu Mbelin is aware and understands the importance of managing water resources, both during the dry and rainy seasons and is able to practice how to make infiltration holes (Biopore holes).